DIABETES COMPLIANCE RESEARCH RESULTS AND PROSPECTS FOR STUDY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Currently, there are a large number of diseases that require close attention from the patient and the doctor due to their resistance (immunity) to treatment, which leads to a significant social burden due to a high vital threat or disability. This requires the patient to strictly adhere to the prescribed treatment. In these diseases, the patient is the “subject” of the treatment process, since the effectiveness of therapy and its results largely depend on his activity, adequacy and purposefulness of behavior. Based on this, we can say that compliance is one of the criteria for the effectiveness of diagnostic and treatment measures. Since in the process of treatment and rehabilitation in patients their adherence to treatment is important, the prognosis and dynamics of the patient’s condition largely depend on this.